Ivermectin-Clorsulon Overdose in Attempting Coronavirus Disease 2019 Prophylaxis: A Case Report - Luc Overholt; Andrea Chau; Rahul Mohan; Sansrita Nepal (Annals of Internal Medicine: Clinical Cases)
With aims of coronavirus disease 2019 (COVID-19) prophylaxis, a 60-year-old woman ingested a formulation of ivermectin and clorsulon, intended for veterinarian use, that contained 30 times the U.S. Food and Drug Administration–approved dose of ivermectin (5.4 mg/kg). She developed altered mental status requiring intubation. Symptoms were similar to other cases of supratherapeutic ivermectin ingestion. Misinformation propagated about COVID-19 prophylaxis and treatment has led to adverse effects both from misuse of medications and disregard of proven options.